In-room cytologic evaluation by trained endosonographer for determination of procedure end in endoscopic ultrasound-guided fine needle biopsy of solid pancreatic lesions: a prospective study in Taiwan - Weng-Fai Wong; Yu-Ting Kuo; Wern-Cherng Cheng; Chia-Tung Shun; Ming-Lun Han; Chieh-Chang Chen; Hsiu-Po Wang (Clinical Endoscopy, 2025)
Background/Aims Endoscopic ultrasound-guided fine needle biopsy (EUS-FNB) is an essential tool for tissue acquisition in solid pancreatic tumors. Rapid on-site evaluation (ROSE) by cytologists ensures diagnostic accuracy. However, the universal application of the ROSE is limited by its availability. Therefore, we aimed to investigate the feasibility of determining the end of the procedure based on the results of in-room cytological evaluation by trained endosonographers (IRCETE). Methods A training course focusing on the cytological interpretation of common pancreatic tumors was provided to the three endosonographers. After training, the decision to terminate EUS-FNB was made based on IRCETE results. The diagnostic accuracy, concordance rate of diagnostic categories, and sample adequacy were compared with those determined by board-certified cytologists and macroscopic on-site evaluation (MOSE). Results We enrolled 65 patients with solid pancreatic tumors, most of whom were malignant (86.2%). The diagnostic accuracy was 90.8% when the end of the procedure was determined based on IRCETE, compared to 87.7% and 98.5% when determined by MOSE and cytologists, respectively (p=0.060). Based on the cytologists’ results, the accuracy of IRCETE in diagnostic category interpretation was 97.3%. Conclusions In the absence of ROSE, IRCETE can serve as a supplementary alternative to MOSE in determining the end of tissue sampling with a high accuracy rate.